Determining Element Accumulations in Turkish Red Pine Used as a Bioindicator for Estimating of Existing Pollution on Both Sides of Bosphorus in İstanbul - Yalçın, İbrahim Ertuğrul; Doğan, İlhan; Özyiğit, İbrahim İlker; Doğan, İlhan; Demir, Göksel; Yarcı, Celal (Parlar Scientific Publications, 2020)
Evergreen Turkish red pine tree shows wide distribution around Aegean and Mediterranean regions in Turkey. Herein work investigated the mineral nutrient status of Turkish red pine as a bioindicator for revealing the impact of existing pollution on both sides of Bosphorus in Istanbul. For this, Al, B, Ca, Cu, Fe, K, Mg, Na and Zn concentrations were determined in unwashed and washed leaves and barks of the plant and soil samples. The standard procedures were applied and the determinations of element concentrations in all samples were done using ICP-OES. The sample collections were performed at five different locations in Istanbul, 4 from the Bosphorus region and one from Prince Island (as control). The highest element concentrations (in mg kg(-1) DW) in plant parts were recorded between 109.10 +/- 1.68 and 120.58 +/- 1.75 for Al, 10.18 +/- 0.14 and 12.52 +/- 0.17 for B, 8765.42 +/- 92.41 and 9600.69 +/- 102.22 for Ca, 10.91 +/- 0.13 and 11.73 +/- 0.16 for Cu, 226.85 +/- 3.01 and 254.07 +/- 3.20 for Fe, 4050.69 +/- 48.51 and 4477.08 +/- 52.34 for K, 794.58 +/- 9.82 and 878.33 +/- 10.07 for Mg, 1255.14 +/- 14.67 and 1374.31 +/- 18.55 for Na and 34.92 +/- 0.49 and 37.25 +/- 0.57 for Zn while the highest element concentrations (in mg kg(-1) DW) in co-located soil samples were measured between 5470.42 +/- 66.48 and 6046.25 +/- 73.54 for Al, 14.86 +/- 0.20 and 16.43 +/- 0.29 for B, 4600.56 +/- 55.22 and 4984.86 +/- 62.71 for Ca, 22.33 +/- 0.36 and 25.07 +/- 0.48 for Cu, 5500.01 +/- 71.05 and 5953.06 +/- 80.16 for Fe, 1819.44 +/- 23.51 and 2029.17 +/- 27.04 for K, 4108.75 +/- 50.77 and 4714.17 +/- 58.09 for Mg, 111.11 +/- 1.82 and 122.08 +/- 2.45 for Na and 117.10 +/- 2.33 and 126.86 +/- 2.61 for Zn.
Keywords: Pinus brutia; Turkish red pine; Bioindicator; Element Uptake; Accumulation